The Ligaments of the Canine Hip Joint Revisited. (12th October 2014) - Casteleyn, C.; den Ouden, I.; Coopman, F.; Verhoeven, G.; Van Cruchten, S.; Van Ginneken, C.; Van Ryssen, B.; Simoens, P.
Summary Numerous conventional anatomical textbooks describe the canine hip joint, but many contradictions, in particular regarding the ligament of the femoral head, are present. This paper presents a brief overview of the different literature descriptions. These are compared with own observations that have resulted in a revised description of the anatomy of the ligament of the femoral head in the dog. To this purpose, the hip joints of 41 dogs, euthanized for reasons not related to this study and devoid of lesions related to hip joint pathology, were examined. It was observed that the ligament of the femoral head is not a single structure that attaches only to the acetabular fossa, as generally accepted, but it also connects to the transverse acetabular ligament and is complemented by a strong accessory ligament that courses in caudal direction to attach in the elongation of the acetabular notch that extends on the cranioventral surface of the body of the ischium. The description of this accessory ligament in conventional anatomical handbooks is incomplete. This description of the accessory ligament of the femoral head could support the research unravelling the etiopathogenesis of hip instability.